Genetic Studies on the Effects of Nanomaterials - Lima, Renata de; Fraceto, Leonardo Fernandes [UNESP]; Duran, N.; Guterres, S. S.; Alves, O. L. (Springer, 2014)
The aim of this chapter is to present some of the principal methodologies used to study the effects of toxic substances on DNA, which can be used to analyze aspects of nanomaterial toxicity. It is not the intention here to undertake an in-depth survey of the topic, but rather to highlight the techniques that can be used in nanotoxicity studies. The available methods for evaluating effects on DNA include genotoxicity tests such as (1) the Allium cepa chromosome aberration test, (2) the comet analysis, (3) the micronucleus test, and (4) the cytogenetic analysis. In addition, this chapter also described the methodologies for analysis of gene expression that can be applied to the effects of nanomaterials. A description of the characteristics of each method is provided, together with results of selected studies that have evaluated the effects of nanomaterials, and a critical discussion of the main advantages and disadvantages of each technique. The chapter also highlights the challenges and future perspectives for studies of the effects of nanostructured materials on DNA.